Innovation in relation to legal position in activity of legal service of state enterprises, establishments andorganizations - Боднарчук, Олег Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the basic questions of innovations are considered in relation to legal position in activity of legal service of state enterprises, establishments and organizations which are directed on perfection of normatively legal base.